2020
DOI: 10.1101/2020.07.31.230466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Memory for stimulus duration is not bound to spatial information

Abstract: Different models have been proposed to explain how the human brain derives an accurate sense of time. One specific class of models, intrinsic models, state that temporal information of a stimulus is represented much like other features such as color and location, bound together to form a coherent percept. Here we explored to what extent this holds for temporal information after it has been perceived and is held in working memory for subsequent comparison. We recorded EEG of participants who were asked to time … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 112 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…This experiment was originally designed to investigate whether maintenance and retrieval of durations from working memory would yield lateralized signals in EEG if the interval was presented on either side of the display. The analyses addressing this question are presented and discussed in a separate article (Kruijne, Olivers, & van Rijn, 2021), so as not to dilute the focus of the research question in the present article. Here, we will focus our analysis on one particular aspect of the task: Stimulus locations either changed or repeated in a fully predictable manner but nevertheless had a robust effect on perceived durations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This experiment was originally designed to investigate whether maintenance and retrieval of durations from working memory would yield lateralized signals in EEG if the interval was presented on either side of the display. The analyses addressing this question are presented and discussed in a separate article (Kruijne, Olivers, & van Rijn, 2021), so as not to dilute the focus of the research question in the present article. Here, we will focus our analysis on one particular aspect of the task: Stimulus locations either changed or repeated in a fully predictable manner but nevertheless had a robust effect on perceived durations.…”
Section: Methodsmentioning
confidence: 99%
“…In a companion article (Kruijne et al, 2021), we analyzed data from the same experiment and specifically aimed to uncover lateralized signals and their relation to time perception. There, cluster-based permutation analyses indicated that lateralized occipital ERPs were also modulated by block type.…”
Section: Erp Components During Intervalmentioning
confidence: 99%
“…This experiment was originally designed in order to investigate whether maintenance and retrieval of durations from working memory would yield lateralized signals in EEG if the interval was presented on either side of the display. The analyses addressing this question are presented and discussed in a separate article (Kruijne et al, 2021), so as not to dilute the focus of the research question in the present article. Here, we will focus our analysis on one particular aspect of the task: stimulus locations either changed or repeated in a fully predictable manner, but nevertheless had a robust effect on perceived durations.…”
Section: Methodsmentioning
confidence: 99%